2015
DOI: 10.1111/neup.12266
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple growth factor signalling pathways is frequent in meningiomas

Abstract: A minority of meningiomas are difficult to treat with surgery or radiotherapy, and chemotherapeutic alternatives are limited. This study aims to better understand pathways that are active in meningiomas, in order to direct future treatment strategies. We investigated the expression and activation of multiple growth factor receptors, their ligands and downstream signalling pathways in 30 meningiomas using immunohistochemistry. Expression was correlated with chromosome 22q loss. Membrane expression of VEGF recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
7
27
0
1
Order By: Relevance
“…There are sparse data on this issue in meningioma tissue (Carroll et al, 1997; Hilton et al, 2016), and according to our findings the activated receptor is expressed at high levels in most tumors. In their study, Hilton et al found significantly higher expression of phosphorylated EGFR in tumor tissues compared with non-neoplastic tissues, and high expression of downstream signaling molecules (Hilton et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…There are sparse data on this issue in meningioma tissue (Carroll et al, 1997; Hilton et al, 2016), and according to our findings the activated receptor is expressed at high levels in most tumors. In their study, Hilton et al found significantly higher expression of phosphorylated EGFR in tumor tissues compared with non-neoplastic tissues, and high expression of downstream signaling molecules (Hilton et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
“…There are sparse data on this issue in meningioma tissue (Carroll et al, 1997; Hilton et al, 2016), and according to our findings the activated receptor is expressed at high levels in most tumors. In their study, Hilton et al found significantly higher expression of phosphorylated EGFR in tumor tissues compared with non-neoplastic tissues, and high expression of downstream signaling molecules (Hilton et al, 2016). The literature is conflicting concerning EGFR and malignancy, as some have found that high expression is positively related to tumor grade (Caltabiano et al, 2013; Diedrich et al, 1995; Halper et al, 1999) whereas others have found the opposite or no differences (Baxter et al, 2014; Guillaudeau et al, 2012; Jones et al, 1990; Kuratsu et al, 1994; Narla et al, 2014; Wernicke et al, 2010).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We also identi ed the EGFR pathway as driving miR-9-1 overexpression in malignant meningioma, via FOS, which is predicted to bind to the promoter/enhancer region of miR-9-1 (43). This is in keeping with previous studies, which have shown that EGF/ERBB2 receptors and FOS are upregulated, and are involved in the molecular process that drives meningioma pathogenesis and/or progression to highergrade tumors (32,(44)(45)(46)(47)(48). FOS knock out experiments supported this observation, resulting in decreased miR-9-1 and increased E-cadherin in malignant KT21-MG1 cells (49,50).…”
Section: Discussionsupporting
confidence: 92%
“…While alterations in the NF2 gene frequently occur, recent molecular genetic studies have identified mutations in AKT1 , SMO , KLF4 , TRAF7 , POLR2A in non-NF2 meningiomas (Brastianos et al, 2013; Clark et al, 2013; Clark et al, 2016). In addition, gene expression analyses have identified AKT as one of the key drivers for meningioma growth (Wang et al, 2012; Hilton et al, 2016). Activation of AKT promotes protein translation initiation, which is dependent upon expression and assembly of several eIF complexes (Jackson et al, 2010; Silvera et al, 2010).…”
Section: Discussionmentioning
confidence: 99%